Determination of Firm Value in Indonesian Food and Beverage Industry - Natsir, Ahmad Mukhta; Natsir, Ahmad Mukhtar; Gusni (IJSM, 2025)
Company value is often used as the main indicator for assessing the success of managerial strategies and future business prospects. This study aims to analyze the influence of profitability, capital structure, and company size on company value in the food and beverage (F&B) sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2018–2024 from 48 companies. This study employs a quantitative approach using secondary data obtained from the annual financial reports of each company, available on the official websites of the issuers and the IDX. The study utilizes panel data regression techniques to explain the factors determining corporate value. The results indicate that, partially, profitability (X₁) and capital structure (X₂) significantly influence company value (Y), while company size (X₃) does not have a significant effect. These findings suggest that internal factors such as profit efficiency and capital structure management are more dominant in determining a company's market value than the size of its assets. This study is expected to provide empirical contributions to investors, company management, and future researchers in understanding the factors that influence company value in the Food and Beverages sector.